Noninfectious pulmonary complications of haematopoietic stem cell transplantation. (24th June 2020) - Haider, Samran; Durairajan, Navin; Soubani, Ayman O.
Haematopoietic stem cell transplantation (HSCT) is an established treatment for a variety of malignant and nonmalignant conditions. Pulmonary complications, both infectious and noninfectious, are a major cause of morbidity and mortality in patients who undergo HSCT. Recent advances in prophylaxis and treatment of infectious complications has increased the significance of noninfectious pulmonary conditions. Acute lung injury associated with idiopathic pneumonia syndrome remains a major acute complication with high morbidity and mortality. On the other hand, bronchiolitis obliterans syndrome is the most challenging chronic pulmonary complication facing clinicians who are taking care of allogeneic HSCT recipients. Other noninfectious pulmonary complications following HSCT are less frequent. This review provides a clinical update of the incidence, risk factors, pathogenesis, clinical characteristics and management of the main noninfectious pulmonary complications following HSCT. Noninfectious pulmonary complications following haematopoietic stem cell transplantation is a major cause of morbidity and mortality in this patient population. There are recent advances in the diagnosis and management of these conditions. http://bit.ly/2FgsIYG